Recycling End-of-Life (EoL) Reverse Osmosis (RO) Membranes into Ultrafiltration Membranes using Potassium Permanganate (KMnO4) for Aquaculture Water Filtration - Putri, Raden Rara Dewi Artanti; Triwibowo, Bayu; Prasetiawan, Haniif; Salwa, Dian Fatimatus; Fauziah, Whilda; Pradana, Daffa Zamiira; Aldiansar , Divifan Armyko (Sainteknol : Jurnal Sains dan Teknologi, 2025)
Sustainable and economical management of aquaculture water is a significant challenge in the fisheries industry. This study aims to convert End-of-Life (EoL) Reverse Osmosis (RO) membranes into Ultrafiltration (UF) membranes using a potassium permanganate (KMnO4) solution as an oxidizing agent to enhance the efficiency of aquaculture water filtration. The conversion process involves immersing the used RO membranes in a 4,5% w/v KMnO4 solution for 3 days at room temperature. Prior to conversion, the membranes were cleaned using a 0,1% w/v Sodium Dodecyl Sulfate (SDS) solution and 0,05 M Ethylenediaminetetraacetic Acid (EDTA) to remove organic and inorganic contaminants. The results showed an increase in water flux from 20 L/m²•h to 50 L/m²•h after conversion. The analysis of aquaculture water quality after filtration using the converted UF membranes showed a significant reduction in Biological Oxygen Demand (BOD) from 5,547 mg/L to 3,817 mg/L, representing 31,2% reduction, and Chemical Oxygen Demand (COD) from 29,91 mg/L to 24,22 mg/L, representing 19% reduction. The membranes were highly effective in removing coliforms, achieving a 100% reduction from 180 MPN/100mL to 0 MPN/100mL. The values of DO and TDS decreased by only about 2%, salinity values remained unchanged, while total ammonia increased. The conversion process increases efficiency filtration, reduces operational costs, and decreases membrane waste.